HLA-A is a Predictor of Hepatitis B e Antigen Status in HIV-Positive African Adults - Matthews, Philippa C; Carlson, Jonathan M.; Beloukas, Apostolos; Malik, Amna; Jooste, Pieter; Ogwu, Anthony; Shapiro, Roger; Riddell, Lynn; Chen, Fabian; Luzzi, Graz; Jesuthasan, Gerald; Jeffery, Katie; et al. (The Journal of Infectious Diseases, 2015)
Outcomes of chronic infection with hepatitis B virus (HBV) are varied, with increased morbidity reported in the context of human immunodeficiency virus (HIV) coinfection. The factors driving different outcomes are not well understood, but there is increasing interest in an HLA class I effect. We therefore studied the influence of HLA class I on HBV in an African HIV-positive cohort. We demonstrated that virologic markers of HBV disease activity (hepatitis B e antigen status or HBV DNA level) are associated with HLA-A genotype. This finding supports the role of the CD8+ T-cell response in HBV control, and potentially informs future therapeutic T-cell vaccine strategies.